(untitled) (Revista Argentina de Musicología, 2022)
Starting with a section on The Decameron and Boccaccio’s vision of resilience through storytelling and musicking, this essay explores the new musical spaces (apartments, windows, balconies, balconies-as-viewed-online, deserted concert halls, streaming events from homes, split screen videos, and so on) that emerged during the first Covid-19 lockdown. It discusses the literature on how people listened to music in their private spaces to cope with the pandemic, and opposes it to media representations of music as a public remedy for an ailing social bond. It addresses the quarantined musicians’ self-expression through dedicated music videos and streaming concerts, and interrogates the prevalence of humor and optimism, in the context of the suffering and death caused by the disease. It also suggests the disruptive effect of the pandemic on traditional ontologies of music, given the difficulty of saying where all these practices under lockdown were actually located.